Work in Progress Creation and Staging of Musical Work Based on Diversity of Traditional Show Art and Ritual in North Sumatera - Khair Amal, Bakhrul; Suroso, Panji; Supsiloani, Supsiloani; Soleh Purba, Anwar (Opción, 2019)
This research is oriented towards the development of the Group of Expertise Lecturer creation in the music education program of the Medan State Uni- versity. Based on the results of internal monitoring conducted by the team of Quality Assurance Education Department of Sendratasik FBS Medan State University was found that: the results of learning creation and staging of mu- sical works are still oriented to popular music culture sources. Learning has not made much use of a source of cultural diversity owned by the community in North Sumatera. The diversity of performing arts and rituals in North Su- matra, is considered as important and can be used as learning resources, espe- cially the creation of music. The source of this diversity will then be excavated and in exploration in discovering the concept – a new concept of creation and staging of musical works in the music education program FBS of Medan State University. The method used in this research is with a qualitative approach. The process of data and information search is done in a deacon to know in full and complete about the diversity of art traditions and rituals in North Suma- tra. The data collected comes from two sources: primary data and secondary data. Primary data is obtained through a depth interview technique and par- ticipant observation. The amount of informant is not limited throughout the required data is still needed to answer the purpose of this research. Secondary Data is obtained from related agencies and related governmental organiza- tions. The results achieved in this study are: 1) produced formulation of Kon- sef Work in progress music creation based diversity of traditional performing arts and ritual in North Sumatra. 2) made findings of Model packaging performance Work in the progress of the creation of musical works based diversity on traditional perform- ing arts and rituals in North Sumatra. 3) created a number of twelve new musical compositions by students of the Education School of Music art FBS Medan State University which based on the diversity of traditional performing arts and rituals of North Sumatera quality and potentially to be proposed gaining HaKi and can be accountable academically.